Tindak Pidana Kejahatan Pencucian Uang (Money Laundering) dalam Pandangan KUHP dan Hukum Pidana Islam - Geno, Ali (Sharia Faculty Islamic Economic Law Study Department, 2019)
Money Laundering is an attempt to hide or disguise the origin of money or assets resulting from a criminal act through various financial transactions so that the money or assets appear as if they came from legal activities. There are three stages taken to